The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s13053-021-00166-1
|View full text |Cite
|
Sign up to set email alerts
|

Recontacting non-BRCA1/2 breast cancer patients for germline CHEK2 c.1100del pathogenic variant testing: uptake and patient experiences

Abstract: Background CHEK2 has been recognized as a breast cancer risk gene with moderate effect. Women who have previously tested negative for a BRCA1/2 gene germline pathogenic variant may benefit from additional genetic testing for the CHEK2 c.1100del pathogenic variant. The aims of this study were: 1) to assess the uptake of an active approach by recontacting BRCA1/2-negative women for additional CHEK2 c.1100del testing on stored DNA-samples and 2) to explore patients’ experiences with this approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These participants did not express negative feelings about being recontacted despite the unexpectedness of the contact and the potential past di culties of coping with a TOP. Previous studies also con rmed mainly positive attitudes towards recontacting (17)(18)(19)(20)(21)26). However, the number of qualitative studies exploring in depth the experience of being recontacted is scarce.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These participants did not express negative feelings about being recontacted despite the unexpectedness of the contact and the potential past di culties of coping with a TOP. Previous studies also con rmed mainly positive attitudes towards recontacting (17)(18)(19)(20)(21)26). However, the number of qualitative studies exploring in depth the experience of being recontacted is scarce.…”
Section: Discussionmentioning
confidence: 79%
“…A few studies have been published in patients with different genetic conditions, more speci cally in deceased children with a mitochondrial disorder (19), children with intellectual disability (18), hereditary cancer patients (20) and patients with varying genetic disorders (21). In general, these empirical studies describe a mainly positive feeling (17)(18)(19)(20)(21), however more indepth exploration of patients' experiences with recontacting is lacking. On the contrary, personal motivations for pursuing genetic testing have been extensively investigated in other contexts such as patients with Huntington's disease and hereditary cancer syndromes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, of the 14 studies that included the CHEK2 gene for screening in this review, only three were identified the c.1100delC variant [ 16 , 18 , 44 ]. This mutation has been described in less heterogeneous populations, as in studies conducted in the Netherlands that described the increased risk of breast cancer observed in patients with CHEK2 1100delC and another study that reported 4% of their tested patients carrying this pathogenic variant [ 64 , 65 ]. Studies show that carriers with a family history of breast cancer are at 2–3 times greater risk when breast cancer is associated with the CHEK2 c.1100delC mutation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%